Gambaran Burnout Syndrome pada Tenaga Kesehatan di RSUD Kota Palangka Raya: Description of Burnout Syndrome in Health Workers in Palangka Raya City Hospital - Jeikawati Jeikawati; Dian Purnama Sari; Suprihatini Suprihatini; Faradila Faradila; Syamsul Arifin (Borneo Journal of Medical Laboratory Technology, 2023)
Corona Virus Disease 2019 (COVID-19) was first reported in Indonesia on March 2, 2020, with a total of two cases, and data for March 31, 2020, showed confirmed cases totaling 1,528 cases and 136 deaths, the highest in Southeast Asia. As of April 24, 2022, there were 509,259,261 cases and 6,242,490 deaths worldwide, while in Indonesia, there were 6,044,150 cases and 156,100 deaths. Burnout syndrome is the inability to deal with stress at work effectively and is more associated with chronic stress due to everyday events than at any particular moment. Individual characteristics, such as personality, values, goals, age, educational level, and family situation, can interact with environmental and occupational risk factors, which can exacerbate or help combat these events. Based on the results of research conducted in months based on characteristics consisting of age, gender, last education, marital status, and years of service of health workers. With this type of research, a quantitative descriptive study using a cross-sectional approach. With the results of the research showing health workers who have mild burnout syndrome and with this research it is hoped that this will become a reference for the City Hospital to maintain the health of employees within the scope of the hospital.